Hubungan Asupan Zat Gizi Dan body Image Dengan Kejadian Kekurangan Energi Kronis ( KEK) Pada Remaja Puteri Di SMAN 1 Bangkinang - Chania, Rani; Harahap, Dewi Anggriani; Lasepa, Wanda (Evidence Midwifery Journal, 2024)
Nutritional problems are prone to occur in the adolescent age group. Adolescents are an age group where specific nutritional problems occur, especially Anemia and Chronic Energy Deficiency (CED). Nutrient intake such as energy, protein and Body Image intake can affect the occurrence of chronic energy deficiency in adolescents. The purpose of this study was to determine the relationship between nutrient intake and Body Image with the incidence of Chronic Energy Deficiency (CED) in female adolescents at SMAN 1 Bangkinang. This type of research is quantitative using a cross-sectional study approach research design. The research tools are questionnaires and LILA. The study was conducted on June 10 - June 22, 2024 with a sample of 52 female students obtained by stratified random sampling. The results of the univariate analysis showed that out of 52 female students, 29 female students (55.8%) had insufficient energy intake, 32 female students (61.5%) had insufficient protein intake, 33 female students (63.5%) were dissatisfied with their body shape and 29 female students (55.8%) had CED status. The results of the bivariate analysis showed a relationship between energy intake (? = 0.000), protein (? = 0.008) and body image (? = 0.003). The conclusion is that there is a relationship between nutrient intake and body image with KEK. It is expected that female students consume food intake containing nutrients to prevent an increase in KEK and minimize the occurrence of KEK in adolescence.